(untitled) (The Journal of Interdisciplinary Human Studies, 2026)
This article analyzes the methodological evolution of refutation literature developed against Hadith rejection in both classical and modern periods. The study provides a comparative analysis of three fundamental works of Islamic jurisprudence and Hadith science: Imam al-Shāfiʿī’s Jimāʿ al-ʿIlm, Ibn Qutayba al-Dīnawarī’s Taʾwīl Mukhtalif al-Ḥadīth, and Muḥammad Abū Shahba’s Al-Difāʿ ʿan al-Sunna. For the first time, the interconnection and developmental stages of legal-methodological (al-Shāfiʿī), logical-linguistic (Ibn Qutayba), and historical-factual (Abū Shahba) refutation styles are revealed. The article also addresses modern doubts concerning the personality of Abū Hurayra (r.a.) and the recording of Hadiths (tadwīn), providing scientific responses based on classical methodology.